El Conde de Morphy (1836-1899) en la Corte de los Borbones. Historia de una familia irlandesa en España (ss. XVIII-XIX) - Beatriz García-Álvarez de la Villa (Estudios Irlandeses, 2019)
In recent times there has been an increasing interest in the study of foreign groups which were part of the circle of influence of Spanish monarchs. The role of these groups in Spanish society has also been a matter of concern. Irish exiles in Spain have been the subject of analysis because of their connection to the elites in power. In the present study, the focus lies on one particular Irish family, the Murphys, in order to ascertain their social and economic progress throughout different generations as well as their level of integration in Spain. The fidelity shown to the Spanish crown, grounded on the Catholic faith and on a record of services to the monarchy, was instrumental for Guillermo Morphy, later Count of Morphy, to be chosen as a trustworthy individual at the court of the Bourbon Dinasty. As a tutor and accompanying gentleman, he would guide the education of Prince Alfonso on solid moral and intellectual principles. When the prince was crowned King as Alfonso XII, he named Guillermo Morphy as his personal secretary. From this position, the Count of Morphy exerted a powerful influence, carrying out several projects on political reform.